Electrochemically-initiated polymerization of reactive monomers via 4-fluorobenzenediazonium salts. Issue 41 (30th September 2021) - Molle, Edgar; Frech, Stefan; Grüger, Tilman; Theato, Patrick
Abstract : We report on the electrochemically-initiated polymerization of reactive monomers using a fluorine-labelled aromatic diazonium salt in an undivided cell setup with subsequent post-polymerization modifications of the intact reactive moieties. Abstract : The straightforward electrochemically-initiated radical polymerization of three reactive monomers, i.e. 2, 6-difluorophenyl acrylate (DFPA), pentafluorophenyl acrylate (PFPA), and glycidyl methacrylate (GMA), using a simple commercially available electrochemical setup for the generation of initiating radical species from 4-fluorobenzenediazonium tetrafluoroborate upon electrochemical cathodic reduction is reported. The use of a fluorine-labelled initiator allowed for the determination of number-average molar masses M n of fluorine-containing polymers by 19 F NMR spectroscopy in addition to size-exclusion chromatography. The obtained polymers were thereafter successfully subjected to post-polymerization modifications in order to emphasize the applicability of this polymerization method in regard to highly reactive monomers.